A Critical Analysis of Amina Wadud’s Feminist Hermeneutics in Qur’anic Interpretation - Ibrahim Hasan Ray (Pascasarjana UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
This study examines Amina Wadud's feminist hermeneutics method in reading the Qur'an, focusing on her efforts to interpret the text with an awareness of the social context and experiences of women as subjects of interpretation. The research gap that this study aims to fill is the lack of studies in Indonesia that systematically analyze the methodological framework and ethical foundations of tawhid in Wadud's feminist hermeneutics, as most previous studies have been descriptive in nature and have not critically linked the methodological, ethical, and implicative dimensions of feminist readings of the Quran. This article positions itself to go beyond a general presentation of Wadud's thinking by offering a conceptual analysis that highlights how Wadud